2001
DOI: 10.1016/s0002-9440(10)64069-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-Induced Vasculopathy in the Murine Conceptus Is Mediated via Reductions of VEGF-A Expression and VEGF Receptor Activation

Abstract: Major congenital malformations, including those affecting the cardiovascular system, remain the leading cause of mortality and morbidity in infants of diabetic mothers. Interestingly, targeted mutations of several genes (including VEGF and VEGF receptors) and many teratogenic agents (including excess D-glucose) that give rise to embryonic lethal phenotypes during organogenesis are associated with a failure in the formation and/or maintenance of a functional vitelline circulation. Given the similarities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 44 publications
8
69
2
Order By: Relevance
“…Although the effect of hyperglycemia on angiogenesis is often presented as a stimulatory one, on the basis of what is observed in the late phase of diabetic retinopathy, defective angiogenesis has been observed in different models such as wound healing (20,21), embryonic growth (7,22), and transplantation of avascular islets of Langerhans (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the effect of hyperglycemia on angiogenesis is often presented as a stimulatory one, on the basis of what is observed in the late phase of diabetic retinopathy, defective angiogenesis has been observed in different models such as wound healing (20,21), embryonic growth (7,22), and transplantation of avascular islets of Langerhans (23).…”
Section: Discussionmentioning
confidence: 99%
“…impaired angiogenesis (7,22). In the model we used, a short-term, modest hyperglycemia without hypoinsulinemia was found to decrease embryonic angiogenesis in vivo.…”
Section: Diabetes Vol 53 March 2004mentioning
confidence: 99%
See 2 more Smart Citations
“…In the remnant kidney model, Kang et al (10) observed a strong correlation between the number of peritubular capillaries and tubular VEGF expression. Changes in VEGF production have been also studied under hypoxic and diabetic conditions, yielding some controversial findings (11,12).…”
mentioning
confidence: 99%